Особливості надання стоматологічної допомоги пацієнтам зі злоякісними новоутвореннями під час хіміотерапії - Філон, А. М.; Возний, Олександр Вікторович; Колеснік, Олексій Петрович; Филон, А. Н.; Возний, А. В.; Колесник, А. П.; Filon, A. M.; Vozniy, O. V.; Kolesnik, O. P. (Українська медична стоматологічна академія, 2019)
Хіміотерапевтичне лікування найчастіше застосовується для лікування злоякісних новоутворень. Дана методика може викликати специфічні стоматологічні ускладнення. Мета дослідження. У даній статті ми вирішили систематизувати найбільш розповсюджені стоматологічні ускладнення хіміотерапевтичного лікування хворих на онкологічні захворювання. Об’єкт і методи дослідження. Було проведено пошук у базах даних: PubMed-Medline, Cochrane Library і Scopus за допомогою ключових слів. Результати дослідження. Хіміотерапевтичне лікування онкологічних захворювань може привести до ускладнень у вигляді гострої стоматотоксичності. Перспективи подальших досліджень. Необхідно вивчити розповсюдженість стоматологічних ускладнень хіміотерапії та умови, за яких вони виникають. Резюме. Химиотерапевтическое лечение чаще всего применяется для лечения злокачественных новообразований. Данная методика может вызвать специфические стоматологические осложнения. Цель исследования. В данной статье мы решили систематизировать наиболее распространенные стоматологические осложнения химиотерапевтического лечения больных онкологическими заболеваниями. Объект и методы исследования. Был проведен поиск в базах данных: PubMed-Medline, Cochrane Library и Scopus с помощью ключевых слов. Результаты исследования. Химиотерапевтическое лечение онкологических заболеваний может привести к осложнениям в виде острой стоматотоксичности. Перспективы дальнейших исследований. Необходимо изучить распространенность стоматологических осложнений химиотерапии и условия, при которых они возникают. Abstract. Today in Ukraine, 800,000 people have oncologic diseases. According to the forecast by 2020, the number of those who first felt ill with cancer could reach 200,000 per year, and the total number of cancer patients will significantly exceed one million people. In Zaporozhe region 2012-2014, for every 100 thousand people, about 450 cases of manifestation of oncological diseases were registered annually. Сhemotherapy is rapidly changing on the basis of protocols of evolution and quality improvement, and the introduction of new therapeutic approaches. Dental treatment before, during and after anticancer chemotherapy requires specialist knowledge. The purpose of a dental examination before chemotherapy is to determine an existing or potential infection of the oral cavity. Control of infection of the oral cavity should be prescribed before the start of chemotherapy, because preventing complications is much easier than then to deal with its consequences. Object and methods. In this article, we decided to highlight the most common dental complications that were the purpose of our study. There was a comprehensive search of the PubMed-Medline, Cochrane Library and Scopus databases that crossed the key words «oral mucositis», «prevention» and «treatment» with the terms «oncology» «chemotherapy» and «radiation therapy», «xerostomia», «dysgeusia» 368 articles were received, of which 136 corresponded to the inclusion criteria. Results. Major complications in the oral cavity and side effects of chemotherapy are associated with such conditions as existing intrauterine pathology, depolymerized teeth, severe periodontal diseases and inflammations of the mucosa caused by chemotherapy. Indeed, mouth infection with dental caries, intraosseous pathology, such as cysts or pronounced periodontal diseases can lead to the development of life-threatening infections and feverish conditions in chemotherapy-dependent patients. Such infections may create the need to interrupt chemotherapeutic treatment, and therefore, it can make a compromise outcome of the treatment of a cancerous tumor.
Особенности оказания стоматологической помощи пациентам со злокачественными новообразованиями при химиотерапии
Features of rendering dental care to patients with malignancies during chemotherapy
Keywords: оральний мукозит; профілактика і лікування термінами «онкологія», «хіміотерапія»; ксеростомія; дисгезія; оральный мукозит; профилактика и лечение терминами «онкология», «химиотерапия»; ксеростомия; дисгезия; oral mucositis; prophylaxis and prevention with the terms «oncology», «chemotherapy»; xerostomia; dysgesia